A computational analysis of the vibrational levels of molecular oxygen in low-pressure stationary and transient radio-frequency oxygen plasma. (10th March 2016) - Kemaneci, Efe; Booth, Jean-Paul; Chabert, Pascal; van Dijk, Jan; Mussenbrock, Thomas; Brinkmann, Ralf Peter
Abstract: Vibrational levels of molecular oxygen, O2 ( v < 42), are investigated in continuous and pulse-modulated low-pressure radio-frequency oxygen plasma with a global modelling approach. The model is benchmarked against a variety of pressure-, power- and time-resolved measurements of several inductive and asymmetric capacitive discharges available in the literature, and a good agreement is obtained. The sensitivity of the model with respect to the vibrational kinetics, the wall reactions and the spatial inhomogeneity of the charged particles are presented. The simulations without the vibrational levels are also shown for the sake of comparison.